Co-Administration of Conjugated Linoleic Acid and Rosiglitazone Increases Atherogenic Co-Efficient and Alters Isoprenaline-Induced Vasodilatation in Rats Fed High Fat Diet - Chai, Boon Kheng; Lau, Yeh Siang; Loong, Bi Juin; Mustafa, Mohd Rais; Ting, K.N.; Murugan, Dharmani Devi; Mohankumar, Suresh Kumar (Czech Academy of Sciences, Institute of Physiology, 2018)
The cis(c)-9, trans(t)-11 (c9,t11) and t10,c12 isomers of conjugated linoleic acid (CLA) have been reported as agonists of peroxisome proliferator-activated receptor (PPAR) and beneficial in lipidemia and glycemia. However, it is unclear whether CLA isomers enhance or antagonize effects of conventional drugs targeting PPAR. Male Sprague-Dawley rats were fed high fat diet (HFD) for 8 weeks and treated without or with CLA, rosiglitazone or both for 4 weeks. Oral glucose tolerance and surrogate markers of insulin resistance were not significantly different for all treatments compared to untreated normal diet (ND) or HFD group, except lipoprotein levels. The combination of CLA and rosiglitazone had suppressed levels of low and high density lipoproteins (46 % and 25 %, respectively), compared to HFD-alone. Conversely, the atherogenic co-efficient of the animals received HFD or HFD+rosiglitazone+CLA was 2-folds higher than ND, HFD+rosiglitazone or HFD+CLA. Isolated aortic rings from the combined CLA and rosiglitazone treated animals were less sensitive to isoprenaline-induced relaxation among endothelium-denuded aortas with a decreased efficacy and potency (R max =53±4.7 %; pEC50=6±0.2) compared to endothelium-intact aortas (R max =100±9.9 %; pEC50=7±0.2). Our findings illustrate that the combination of CLA and rosiglitazone precede the atherogenic state with impaired endotheliumindependent vasodilatation before the onset of HFD-induced insulin resistance.